Safety and Efficacy of l‐histidine monohydrochloride monohydrate produced by fermentation using Escherichia coli KCCM 80212 as a feed additive for all animal species. (10th November 2020) - ,; Bampidis, Vasilios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on l ‐histidine monohydrochloride (HCl) monohydrate produced by fermentation using Escherichia coli KCCM 80212 when used as a nutritional additive in feed for all animal species. The production strain is genetically modified. The production strain and its recombinant DNA were not detected in the final product. l ‐Histidine HCl monohydrate manufactured by fermentation using E. coli KCCM 80212 does not give rise to any safety concern regarding the genetic modification. The use of l ‐histidine HCl monohydrate produced by fermentation using E. coli KCCM 80212 is safe for the target species when used as a nutritional additive to supplement the diet in appropriate amounts to cover the requirements, depending on the species, the physiological state of the animal, the performance level, the environmental conditions, the background amino acid composition of the unsupplemented diet and the status of some essential trace elements such as copper and zinc. l ‐Histidine HCl monohydrate produced using E. coli KCCM 80212 supplemented at levels appropriate for the requirements of the target species is considered safe for the consumer. l ‐Histidine HCl monohydrate produced by E. coli KCCM 80212 is a skin sensitiser. There is a risk for persons handling the additive from the exposure to endotoxins by inhalation. The additive under assessment is not irritant to skin or eyes. The use of l ‐histidine HCl monohydrate produced using E. coli KCCM 80212 in animal nutrition is not expected to represent a risk to the environment. l ‐Histidine HCl monohydrate is considered an efficacious source of the essential amino acid l ‐histidine for non‐ruminant animal species. For the supplemental l ‐histidine to be as efficacious in ruminants as in non‐ruminant species, it would require protection against degradation in the rumen.